The Implementation of Good Corporate Governance on Company Financial Performance - Tarigan, Bram Timothy; Yuliansyah, Yuliansyah (Riset Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This study aims to obtain empirical evidence on the effect of good corporate governance implementation on the financial performance of companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2022 period. Methodology/approach: Using the purposive sampling method as a sampling technique, so that a population of 37 companies was obtained. To determine the magnitude of the influence of good corporate governance on the company's financial performance, regression analysis, correlation analysis of the F test and t test and analysis of the coefficient of determination are used. Results/findings: The results of this study indicate that the variables of good corporate governance do not have a significant effect on company value. Conclusions: This study is a review of several journals that aim to examine the influence of independent boards of commissioners, managerial ownership, institutional ownership, foreign ownership, and audit committees on financial performance. This study took a sample of manufacturing companies in the consumer goods sector during the period 2018-2022. Limitations: The limitations of this study are that there are only two fundamental factors, namely, total asset turnover and corporate governance, and the sample used is processed food industry companies that do not represent all sub-sectors of other companies. Contribution: This study can be used as a reference for future research, especially research corporate governance.